A polyethylene polyamine and a method for its preparation
Patent Information
- Application Number
- CN202611188225.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-27
AI Technical Summary
[0030]1、采用Mg1Ti1/v-Al2O3非均相催化床层,为微通道反应器提供足够路易斯酸强亲电活性位点,加速C-Cl键的活化与胺化反应进程,在本申请测试条件下表现为较高转化率和选择性。在温和的反应条件下,二氯乙烷的反应总转化率最高达95.1%,高沸点多胺产品的选择性最高达71.3%。
Smart Images

Figure CN122977968A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fine chemical technology, specifically to a polyethylene polyamine and its preparation method. Background Technology
[0002] Polyethylene polyamines are high-value nitrogen-containing linear long-chain intermediates in the fine chemical industry, widely used in the manufacture of high-performance epoxy curing agents, paper wet strength agents, and chelating agents. Currently, the main industrial method for their production is the dichloroethane amination process. This process is typically carried out under high pressure in the liquid phase, where dichloroethane (EDC) undergoes a nucleophilic substitution reaction with ammonia to construct the ethyleneamine chain segment.
[0003] However, both current research and industrial practice face a core problem: the highly complexed polyethylene polyamine products cause severe nucleophilic chelation loss to transition metal catalysts, leading to poor long-term catalyst stability. To balance reaction conversion and long-chain linear selectivity, supported transition metal catalysts are often introduced; however, polyethylene polyamine molecules are rich in high-density lone-pair nitrogen atoms, making them typical strongly complexed, strongly basic ligands. During continuous-flow amination reactions, high-concentration, long-chain polyamine products undergo active chelation with the active metal centers on the catalyst surface, stripping metal atoms as complexes and carrying them into the feed stream. This not only results in a high metal loss rate during continuous operation, causing localized coarsening, collapse, and rapid deactivation of the catalyst bed, but also contaminates the refined polyamine product obtained from subsequent fractionation. Therefore, how to completely block the directional chelation loss of long-chain polyamines to the catalytic active centers while ensuring efficient activation of carbon-chlorine bonds is a critical technical bottleneck that urgently needs to be overcome in the continuous-flow catalytic preparation of high-boiling-point polyamines from dichloroethane.
[0004] Therefore, a polyethylene polyamine and its preparation method are proposed. Summary of the Invention
[0005] The purpose of this invention is to provide a polyethylene polyamine and its preparation method. This method utilizes an integrated multi-channel microreactor with a Mg1Ti1 / v-Al2O3 heterogeneous catalytic membrane on its inner wall. By introducing exogenous polyvinylpyrrolidone into the loading process and subjecting it to subsequent heat treatment and in-situ pre-activation in the liquid phase, a compact internal structure is formed. Simultaneously, the material is continuously passed through a pre-mounted dual-field fluid physical polarization chamber and tangentially injected into the microchannel reactor for catalytic amination. A catalyst-free high-temperature hollow tube thermal condensation section is cascaded in the subsequent stage. This accelerates the amination process, increases the total conversion rate of dichloroethane, and achieves high selectivity for linear polyamines. It also cuts off the deamination and cyclization pathway, significantly reducing byproducts such as piperazine. Furthermore, the microchannel exhibits low cumulative total metal loss rate and good stability after 50 hours of continuous operation.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] Step 1: Catalytic Membrane Construction and In-situ Activation of System Assembly: The prepared supported defect lattice confined catalyst powder, silica sol binder, and polyvinyl alcohol rheology modifier were mixed in deionized water at a mass ratio of 100:15:3. The mixture was sheared and stirred to prepare a coating slurry with a solid content of 20 wt%. This slurry was uniformly coated onto the inner wall of the microchannels of the integrated multi-channel microreactor using a vacuum impregnation method. The slurry was dried at 100°C for 2 hours and then calcined at 400°C for 3 hours under a nitrogen atmosphere to form a stable catalytic membrane. The pressure-resistant microchannel reaction system was then assembled. Before introducing the material, an ammonia solution containing potassium hydroxide was continuously pumped countercurrently into the microchannels for in-situ liquid-phase pre-activation. The polyvinyl alcohol in the raw material underwent confined carbonization after calcination with N2 at 400°C, forming a porous carbon framework doped in the SiO2 network in situ. The final catalytic membrane was composed of the active component, carbon material, and the SiO2 network.
[0008] Step 2: Material dual external field strength mass transfer fluid physical polarization: Refined dichloroethane and ammonia are thoroughly mixed according to the molar ratio and continuously injected into the fluid physical polarization chamber. The acoustic transducer on the outside of the chamber is turned on to perform dual-frequency resonance, and the continuous microwave generator is turned on to perform fluid physical polarization, so as to obtain polarized material fluid.
[0009] Step 3: Continuous flow microchannel catalytic amination in a confined temperature field: The polarized material fluid is continuously and tangentially injected into a microchannel reactor packed with a pre-activated catalyst bed to carry out the microchannel catalytic amination reaction and obtain the microchannel amination effluent.
[0010] Step 4: Cascaded Empty Tube Thermal Coupling Growth and Dilution Desalination Distillation: The microchannel amination effluent is directly introduced into the catalyst-free high-temperature empty tube thermal condensation section for continuous thermal coupling segment polymerization. After the reaction stabilizes, the reaction effluent is first sent to a high-efficiency flash evaporator to remove most of the water and excess ammonia, resulting in a concentrated salt-containing polyamine residue. Subsequently, 2-3 times its mass of anhydrous ethanol is continuously and precisely pumped into this concentrated polyamine residue as an anti-solvent crystallization desalting solvent for the high-salt system. The temperature is then reduced to 20°C through a cascaded heat exchanger, allowing the ammonium chloride and potassium chloride crystals, byproducts of the reaction, to fully separate under the high anti-solvent environment of ethanol. The crystals are then continuously centrifuged using a continuous flow industrial centrifuge to remove solid salt particles. The resulting clear liquid phase is continuously introduced into a desolventizing tower for flash evaporation to remove excess ammonia and for recycling of the anhydrous ethanol solvent. Finally, the liquid is sent to a vacuum fractionation system for vacuum distillation at a temperature above 200°C and a pressure of 10 mmHg, to obtain the high-boiling-point polyamine product.
[0011] The fluid physical polarization cavity in step two is composed of a quartz / stainless steel double-wall structure, with the acoustic transducer attached to the outer side of the outer metal wall, and the microwave feed port introduced through the quartz window on the side wall of the cavity.
[0012] Preferably, in step one, the supported defect lattice-confined catalyst is labeled Mg1Ti1 / v-Al2O3, where v represents an oxygen vacancy defect; its preparation method is as follows: the heating rate of solid aluminum isopropoxide in a high-purity argon atmosphere is adjusted to 2℃ / min-10℃ / min, for example, it can be 2℃ / min, 5℃ / min, 8℃ / min, 10℃ / min, etc., heated to 550℃-650℃, and continuously calcined for 3h-6h to carry out a thermal decomposition and layering reaction, cooled and ground until the median particle size D50 is 5μm-15μm to obtain alumina intermediate powder; the alumina intermediate is then... The powder was placed in a 1:1 volume ratio of isopropanol and water and subjected to liquid-phase acoustic exfoliation at a power of 300W-500W for 4-10 hours to obtain thin two-dimensional Al2O3 nanosheets with a thickness of 1.0nm-1.6nm. The two-dimensional Al2O3 nanosheets were then fed into the cavity of an inductively coupled plasma device, and high-purity argon gas was introduced. The working pressure of the cavity was controlled at 30Pa-50Pa, and the working power was set at 150W-350W to perform argon plasma directional bombardment and lattice oxygen atom exfoliation treatment for 5min-25min to obtain a modified alumina carrier rich in oxygen vacancy defects.
[0013] Preferably, in step one, the process of supporting the metal in the defect-confined catalyst is as follows: A mixed metal salt aqueous solution is prepared with a magnesium to titanium atomic molar ratio controlled at 1:1; the modified alumina support rich in oxygen vacancy defects is uniformly dispersed in anhydrous ethanol using a shear emulsifier, with the dispersion speed controlled at 800 r / min-1500 r / min; an exogenous functional organic locking agent is introduced: exogenous functional organic polyvinylpyrrolidone (PVP) is added to the system, with its mass controlled at 4%-6% of the mass of the defect-modified alumina support. Utilizing the strong nucleophilic coordination ability and amphiphilicity of the lactam group (-NC=O) in the PVP structure, the PVP... The P long chains are fully spread and extended on the surface of the thin nanosheets and synergistically complex with oxygen vacancies; the material temperature is controlled at -5℃ to 5℃, and the mixed metal salt aqueous solution is slowly added dropwise at a rate of 0.2 mL / min to 0.6 mL / min under a mechanical stirring speed of 1000 r / min to 1500 r / min. After the addition is completed, the coordination reaction is continued under light-protected conditions for 2 h to 14 h; wherein, the mixed metal salt aqueous solution is prepared by dissolving magnesium acetate tetrahydrate and titanium tetrachloride in pure water, and the total active metal loading in the catalyst is 2.0% to 8.5% of the total mass of the catalyst, preferably 4.0% to 6.5% based on metal elements.
[0014] Preferably, in step one, the interfacial coordination partial reduction induction and solid-phase heat treatment specifically involves: after the coordination reaction is completed, adding 3% sodium hydroxide solution to the system to adjust the pH value to 11-12, adding a hydrazine hydrate ethanol solution with a concentration of 10 mmol / L-20 mmol / L to the system, and controlling the material temperature in an ice-water bath environment of -5℃ to 5℃ for interfacial coordination and partial reduction induction for 2-4 hours; after the reaction is completed, performing vacuum centrifugation washing 3-6 times, transferring it to a vacuum freeze-drying oven at -60℃ to -50℃ for drying for 24-36 hours, and finally placing the solid product in a tube furnace and heating it to 300℃-600℃ for solid-phase heat treatment for 4-6 hours under the protection of high-purity nitrogen at a flow rate of 100 mL / min-200 mL / min. At high temperature, PVP undergoes localized confined carbonization, generating a heteroatom highly conductive carbon network framework in situ to lock the nanosheets, and obtaining a supported defect lattice confined catalyst after cooling.
[0015] Preferably, in step one, the catalyst coating and in-situ pre-activation specifically involve: controlling the thickness of the catalytic membrane coated inside the integrated multi-channel microreactor to be 50μm-100μm, for example, 50μm, 65μm, 80μm, 100μm, etc.; in the ammonia solution containing potassium hydroxide used for in-situ pre-activation in the liquid phase, the mass fraction of ammonia is 25%-30%, and the mass fraction of potassium hydroxide is 3%-5%; the specific process parameters for continuous pre-activation are: controlling the system activation temperature to be 85℃-95℃, the activation pressure to be 1.2MPa-2.0MPa, and the liquid hourly space velocity to be 3.0h. -1 -6.0h -1 Continuous cyclic immersion and rinsing activation treatment for 2.0h-4.0h.
[0016] Preferably, in step two, the specific process parameters for the external field fluid physical polarization of the material are as follows: the initial molar ratio of the mixed material between refined dichloroethane and ammonia water with a mass fraction of 25%-30% is controlled at 1:12-1:18, for example, it can be 1:12, 1:15, 1:16, 1:18, etc.; the Reynolds number of the material fluid in the fluid physical polarization cavity is controlled at 2100-2800, in the transition turbulent region to achieve efficient external field polarization and interphase mixing; the acoustic transducer adopts a dual-frequency resonance mode with combined frequencies of 60kHz and 100kHz, and the total acoustic power is controlled at 400W-600W; the operating frequency of the continuous microwave generator is locked at 2450MHz, and the constant operating power is controlled at 700W-900W; the flow rate of the material fluid in the fluid physical polarization cavity is regulated to a total residence time of 8s-15s.
[0017] Preferably, in steps three and four, the specific process parameters for the continuous operation of continuous flow catalytic amination and subsequent thermal condensation are as follows: the polarized material fluid is tangentially injected into the microchannel of the microchannel reactor from the polarization chamber, and the fluid is converted to a strictly laminar flow state inside the microchannel, with its liquid hourly space velocity controlled at 15 h⁻¹. -1 -25h -1 The working reaction temperature inside the microchannel reactor is controlled at 125℃-140℃, and the working pressure is controlled at 2.8MPa-3.5MPa. After the reaction fluid flows out of the microchannel, it directly enters the catalyst-free high-temperature hollow tube thermal condensation section. The reaction temperature of the thermal condensation section is controlled to be stably maintained at 175℃-195℃, and the running residence time is controlled at 10min-15min. After dilution with anhydrous ethanol pumped into the system, salt filtration by continuous centrifuge, and solvent removal by flash evaporation, the effluent is finally obtained by vacuum distillation at above 200℃ and under a pressure of 10mmHg through a cascade fractionation system to obtain the high-boiling-point polyamine product.
[0018] Furthermore, the high-boiling-point polyamine products are a mixed linear chain of pentaethylenehexamine, hexaethyleneheptaamine, heptaethyleneoctaamine, octaethylenenonamine, and nonaethylenedecaamine. The total nitrogen content of the products obtained by distillation is stably maintained at 30.2%-33.4%, and the target distillation volume ratio above 200℃ reaches 42%-67%. Moreover, the final specific gravity of the products is controlled within the range of 1.005-1.038, and the measurement temperature conditions are 20℃ relative to 4℃ water.
[0019] Furthermore, in the continuous flow microchannel catalytic application system, when the continuous operation reaction time is ≥50h, due to the catalyst's unique single-point defect lattice coordination structure and the spatial locking effect of PVP polymer, the directional chelation loss of strongly complexed polyamine products to the active center is blocked, so that the cumulative total loss rate of active metals magnesium and titanium in the system discharge material is controlled at a low level of 0.04ppm-0.28ppm.
[0020] The pure solid aluminum isopropoxide used has a purity ≥99.5% and CAS number 555-31-7; magnesium acetate tetrahydrate has a purity ≥99.0% and CAS number 16674-78-5; titanium tetrachloride has a purity ≥99.0% and CAS number anhydrous titanium tetrachloride; polyvinylpyrrolidone (PVP) has a purity ≥99.0%; electronic grade hydrazine hydrate solution has a mass concentration of 80% (aqueous solution basis) and CAS number 10217-52-4; industrial grade refined 1,2-dichloroethane has a purity ≥99.8% and a moisture content ≤100ppm and CAS number 107-06-2; industrial grade pure potassium hydroxide has a purity ≥95.0%, and the polyvinylpyrrolidone (PVP) is specifically type K-30.
[0021] This invention also provides a high-boiling-point polyamine product prepared by any of the above-mentioned process routes. Because the intramolecular cyclization side reaction channels are cut off in situ and the continuous free thermal coupling growth path of residual lower amines is opened, the total mass percentage of cyclic amine byproducts such as 1,4-diazacyclohexane (piperazine), 2-(piperazin-1-yl)ethyl-1-amine, and 2,2'-(piperazin-1,4-diyl)bis(ethyl-1-amine) in the obtained product is reduced and maintained in the range of 1.4%-5.8%. This achieves a directional shift of the product distribution towards the long-chain high-boiling-point linear polyamine range, with a total conversion rate of 78.4%-95.1% for the dichloroethane reaction and a selectivity of 54.1%-71.3% for the high-boiling-point polyamine product.
[0022] In this invention, the conversion rate (%) of dichloroethane and the selectivity (%) of the high-boiling-point polyamine product are both calculated based on the carbon atom conservation (carbon balance) during the reaction process. The formula for calculating the selectivity is as follows:
[0023]
[0024] In the formula: M is the target polyamine, i is the molar yield of the i-th target linear polyamine (pentaethylenehexamine i=5, hexaethyleneheptaamine i=6, heptaethyleneoctaamine i=7, octaethylenenonamine i=8, nonaethylenedecaamine i=9); n represents the number of dichloroethane conversion structural units contained in the target polyamine molecule, that is, the corresponding number of two-carbon segments, pentaethylenehexamine n=5, and so on; the 2 in the denominator indicates that each molecule of dichloroethane provides 2 carbon atoms.
[0025] The overall conversion of dichloroethane and the selectivity of high-boiling-point polyamine products were determined using a gas chromatograph equipped with a flame ionization detector (FID). The effluent suspension at the reactor outlet was collected, filtered through salt, and the mass of the clear liquid phase was accurately weighed. Unreacted 1,2-dichloroethane residues were quantitatively analyzed using high-purity gas chromatographic grade methanol as solvent and an internal standard method (with cyclohexane as the internal standard). The conversion of dichloroethane was calculated based on the conservation of total carbon atoms in the reaction feed. Simultaneously, the polyamine components were separated by capillary column chromatography, and the molar yields of each linear polyamine homologue (pentaethylenehexamine to nonaethylenedecaamine) were quantified. The selectivity of the high-boiling-point polyamine products was calculated using the aforementioned general formula for selectivity, and data were retained to one decimal place.
[0026] The total mass percentage of cyclic amine byproducts was quantitatively analyzed using gas chromatography-mass spectrometry (GC-MS) and high-performance liquid chromatography (HPLC) with external standard method. 1,4-diazacyclohexane (piperazine), 2-(piperazin-1-yl)ethyl-1-amine (aminoethylpiperazine), and 2,2'-(piperazin-1,4-diyl)bis(ethyl-1-amine) in the crude product were separated chromatographically using an HP-5MS weakly polar capillary column. Electron impact spectroscopy (EI) was used for qualitative characteristic ion fragment monitoring. The high-boiling-point cyclic oligomers were fully verified using HPLC, and the total mass percentage of cyclic byproducts was obtained by summing the results. Data were retained to one decimal place.
[0027] The target distillate volume percentage is determined by measuring the total initial volume of the clarified liquid phase of the crude polyamine product (after removal of ammonia, anhydrous ethanol, and desalting). This clarified liquid is then transferred to a vacuum fractionation apparatus equipped with a precision vacuum control valve. The temperature of the distillation column is controlled, and the vapor fraction exceeding 200°C is continuously collected under a vacuum of 10 mmHg and measured in a condenser. The percentage of this target distillate volume relative to the total initial liquid volume is calculated, with the data rounded to one decimal place.
[0028] The cumulative total loss rate of active metals was quantitatively tracked using inductively coupled plasma mass spectrometry (ICP-MS). During a 50-hour continuous operation cycle, all effluent discharged from the device was collected periodically and the total amounts were combined. 1.0 mL of the thoroughly mixed sample fluid was precisely transferred, and a high-purity nitric acid and hydrogen peroxide system was added for microwave digestion. After adjusting the volume, the sample was passed through ICP-MS to determine the mass concentrations of magnesium (Mg) and titanium (Ti). The cumulative total loss of active metals over 50 hours was calculated, and the data were rounded to two decimal places.
[0029] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0030] 1. The use of a Mg1Ti1 / v-Al2O3 heterogeneous catalytic bed provides sufficient Lewis acid electrophilic active sites for the microchannel reactor, accelerating the activation and amination process of the C-Cl bond. Under the test conditions of this application, it exhibits high conversion and selectivity. Under mild reaction conditions, the total conversion of dichloroethane reaches up to 95.1%, and the selectivity of the high-boiling-point polyamine product reaches up to 71.3%.
[0031] 2. The cascade synergy between the pre-stage dual external field fluid physical polarization and the subsequent catalyst-free high-temperature hollow tube thermal condensation section promotes the growth of residual feedstock towards long-chain linear homologues, cutting off the deammoniation cyclization pathway. This reduces the total mass percentage of piperazine and other cyclic amine byproducts and increases the proportion of the target linear polyamine distillate obtained by vacuum distillation at >200℃ and 10 mmHg.
[0032] 3. By introducing exogenous functional organic compound polyvinylpyrrolidone into the loading process, and synergistically using magnesium acetate tetrahydrate and titanium tetrachloride as dual in-situ carbon sources, combined with pre-activation in the liquid phase and subsequent heat treatment, the polymeric rheology modifier is transformed into an erosion-resistant composite carbon network structure under a protective atmosphere. This structure interpenetrates with the SiO2 network, forming a robust structure within the catalytic membrane that resists the continuous erosion and chelation effects of highly complexed long-chain polyamine fluids. The system operates in continuous flow for up to 50 hours with a low cumulative total loss rate of active metals magnesium and titanium, extending the industrial service life of the catalytic system. Attached Figure Description
[0033] Figure 1 This is a flowchart of the preparation method of the polyethylene polyamine of the present invention;
[0034] Figure 2 This is a bar chart comparing the reaction performance of Example 1 of the present invention with that of Comparative Examples 3 and 4.
[0035] Figure 3 This is a graph showing the cumulative total loss rate of active metals in Example 1 and Comparative Example 2 of the present invention under 50 hours of continuous operation.
[0036] Figure 4 This is a trend chart showing the product index changes under the stepwise increase of process parameters in Embodiments 2-10 of the present invention. Detailed Implementation
[0037] The present invention will now be described in detail with reference to specific embodiments.
[0038] Example 1
[0039] 30.000±0.001g of solid aluminum isopropoxide was placed in a covered high-alumina crucible and transferred to a muffle furnace. The crucible was heated to 600℃ at a heating rate of 5℃ / min under a high-purity argon atmosphere and continuously calcined at this temperature for 4 hours to induce a thermal decomposition and layering reaction, yielding a thin, sheet-like alumina intermediate. After cooling to room temperature, the powder was ground using an air jet mill and sieved. 10.000pm0.001g of the intermediate powder with a median particle size D50 of 8.5μm was placed in an open quartz boat and transferred back into a tube furnace. The furnace was then subjected to liquid-phase acoustic exfoliation treatment in a mixed solvent of isopropanol and water (volume ratio 1:1) at 400W for 6 hours to obtain thin two-dimensional Al2O3 nanosheets with a layer thickness of 1.2 to 1.5nm.
[0040] 7.800g of the nanosheet solid powder obtained by the above exfoliation was sent into the cavity of an inductively coupled plasma device, high-purity argon gas was introduced, the working pressure of the cavity was 40Pa, and argon plasma with a power of 250W was used for directional bombardment for 15min to obtain a modified carrier for later use.
[0041] Prepare a 60 mL aqueous solution containing 0.384 g magnesium acetate tetrahydrate and 0.340 g titanium tetrachloride, with the atomic molar ratio of magnesium to titanium controlled at 1:1. The specific preparation method is as follows: First, in a fume hood and ice-water bath environment, measure 50 mL of deionized water and add 0.2 mL of concentrated hydrochloric acid to inhibit premature self-hydrolysis of titanium ions; then, slowly add 0.340 g of high-purity titanium tetrachloride dropwise under vigorous stirring until the system is completely clear and transparent; finally, add 0.384 g of magnesium acetate tetrahydrate crystals, continue stirring to dissolve, and dilute to 60 mL with deionized water to obtain a highly transparent inorganic composite metal salt drop solution; uniformly disperse 7.800 ± 0.001 g of modified carrier prepared in the first step in 300 mL of anhydrous ethanol using a shear emulsifier, then add 0.390 g of polyvinylpyrrolidone (PVP, K-30) and place the mixture in a 0 °C ice-water bath.
[0042] Under stirring at 1200 r / min, 60 mL of a mixed metal salt aqueous solution was added dropwise to the carrier dispersion at a rate of 0.4 mL / min. After the addition was completed, stirring was continued at 0℃ in the dark for 8 h. After stirring, a 10 wt% sodium hydroxide solution was slowly added dropwise to adjust the pH of the system to 11.5. Then, 40 mL of a 15 mmol / L hydrazine hydrate ethanol solution was added at a rate of 2 mL / min. The system was reacted in an ice-water bath for 3 h. The resulting solid product was washed five times by vacuum centrifugation with anhydrous ethanol, and then dried in a vacuum freeze-drying oven at -55℃ for 30 h. The dried solid product was then placed in a quartz tube furnace and subjected to solid-phase heat treatment at 450℃ for 5 h under high-purity nitrogen at a flow rate of 150 mL / min. The catalyst, labeled Mg1Ti1 / v-Al2O3, was obtained after the heat treatment.
[0043] The Mg1Ti1 / v-Al2O3 catalyst powder, silica sol binder, and polyvinyl alcohol rheology modifier prepared above were mixed in deionized water at a mass ratio of 100:15:3, and the mixture was sheared and stirred to prepare a coating slurry with a solid content of 20 wt%. The slurry was uniformly coated onto the inner wall of the microchannels of an integrated multi-channel microreactor using a vacuum impregnation method, controlling the thickness of the internally coated catalytic film to be 65 μm. The film was dried at 100 °C for 2 h, and then calcined and cured at 400 °C for 3 h under a nitrogen atmosphere to form a stable catalytic film. Subsequently, a pressure-resistant microchannel reaction system was assembled.
[0044] Before introducing the main reactants, a liquid-phase in-situ pre-activation solution is continuously pumped countercurrently into the microchannels of the microreactor. The liquid-phase in-situ pre-activation solution contains a mixed aqueous solution of 28 wt% ammonia and 4 wt% potassium hydroxide. The activation temperature is controlled at 90℃, the activation pressure at 1.5 MPa, and the liquid hourly space velocity at 4.5 h⁻¹. -1The system undergoes continuous cyclic immersion and rinsing activation treatment for 3.0 hours to complete the pre-activation in situ of the system.
[0045] Industrial-grade refined 1,2-dichloroethane was thoroughly mixed with 28 wt% ammonia water at an initial molar ratio of 1:15, and continuously injected into a pre-cascaded fluid physical polarization chamber using a high-pressure plunger pump. The Reynolds number of the material flow in the fluid physical polarization chamber was controlled to be 2450, thereby placing it in the transition turbulent region, and the total residence time was adjusted to 12 s.
[0046] Simultaneously, a dual-frequency acoustic transducer and a continuous microwave generator attached to the outside of the fluid physical polarization cavity are activated: the acoustic transducer adopts a dual-frequency resonance mode with combined frequencies of 60kHz and 100kHz, controlling the total acoustic power to 500W; the continuous microwave generator's operating frequency is set to 2450MHz, and its constant operating power is controlled at 800W. Through the combined effect of the superposition of the two external fields, the passing fluid material undergoes transient physical polarization.
[0047] The polarized material fluid was then continuously and tangentially injected into the microchannels of the pre-activated microchannel reactor. By controlling the microchannel size and single-channel flow rate, the Re flow rate within the microchannels was kept in the laminar flow range. The liquid hourly space velocity was controlled at 20 h⁻¹. -1 The working reaction temperature inside the microchannel reactor is stably controlled at 135℃ and the working pressure is controlled at 3.2MPa to carry out the microchannel catalytic amination reaction.
[0048] After the reaction fluid flows out of the microchannel reactor, it is directly introduced into the high-temperature empty tube thermal condensation section without catalyst in the later stage for continuous thermal coupling segment polymerization. The reaction temperature of the thermal condensation section is controlled to be stably maintained at 185℃, and the running residence time is controlled to be 12min, so as to obtain the microchannel amination thermal condensation effluent.
[0049] After the reaction stabilizes, the microchannel amination thermal condensation effluent is first introduced into a pre-dehydration flash evaporator. At 105℃-115℃, over 90% of the water and unreacted excess free ammonia are removed from the effluent. A highly concentrated saline polyamine residue is obtained at the bottom of the column. Subsequently, 2.5 times its mass of anhydrous ethanol is continuously and precisely pumped into this concentrated saline polyamine residue as an anti-solvent crystallization solvent. The solution is cooled to 20℃ via a cascade heat exchanger, forcibly driving the precipitation of reaction byproducts ammonium chloride and potassium chloride crystals in a water-poor, ethanol-rich system. The suspension is then introduced into a continuous flow industrial centrifuge for continuous centrifugation to remove solid salt particles. The resulting clear liquid phase is continuously introduced into a post-distillation column for flash evaporation to remove and recover the anhydrous ethanol solvent for recycling.
[0050] The residue after removing the ethanol solvent is sent to a vacuum fractionation system for vacuum distillation at a temperature above 200°C and a pressure of 10 mmHg to obtain a high-boiling-point polyamine product.
[0051] The continuous flow microchannel catalytic amination system operated stably for 50 hours in Phase I. Based on the carbon balance and carbon atom conservation during the reaction, the overall conversion rate of dichloroethane remained stable at 88.5%, and the selectivity for high-boiling-point polyamine products reached 64.2%.
[0052] In the high-boiling-point polyamine products obtained by distillation, the total nitrogen content remained stable at 32.1%, and the volume percentage of the target distillate (mixed linear chain polyamines such as pentaethylenehexamine, hexaethyleneheptaamine, heptaethyleneoctaamine, octaethylenenonamine, and nonaethylenedecaamine) above 200℃ reached 58.4%, with the final specific gravity of the product at 20℃ being 1.022.
[0053] Analysis by gas chromatography-mass spectrometry (GC-MS) showed that the total mass percentage of cyclic amine byproducts [including 1,4-diazacyclohexane (piperazine), 2-(piperazin-1-yl)ethyl-1-amine, and 2,2'-(piperazin-1,4-diyl)bis(ethyl-1-amine)] in the obtained polyamine products was reduced to 2.6 wt%.
[0054] Metal element tracking of the discharged material was performed using inductively coupled plasma mass spectrometry (ICP-MS), and the cumulative total loss rate of active metals magnesium and titanium was as low as 0.09 ppm over the entire 50-hour operating cycle.
[0055] Examples 2-10 maintain the basic process flow, fluid physical polarization dual external field configuration, downstream thermal condensation series mode, and separation and purification steps consistent with Example 1; however, the following parameters have been adjusted, as shown in Table 1.
[0056]
[0057] Comparative Example 1: The basic preparation and reaction parameters are the same as in Example 1. The only difference is that in the catalyst support preparation in step 2, the two-dimensional Al2O3 nanosheets obtained by exfoliation are directly fed into the subsequent coordination stage, and the directional bombardment treatment of argon plasma in the cavity of the inductively coupled plasma device is eliminated, i.e., t1=0min.
[0058] Comparative Example 2: The basic preparation and reaction parameters were the same as in Example 1. The only difference was that in the active metal loading process in step 3, after dispersing the modified support in anhydrous ethanol, no exogenous functional organic compound, polyvinylpyrrolidone (PVP), was added to the system.
[0059] The difference between Comparative Example 3 and Example 1 is that, in the fluid transport process, after the mixture of dichloroethane and ammonia is continuously injected into the fluid polarization chamber, the acoustic transducer and the continuous microwave generator are not turned on, meaning that the dual external field power and working residence time are both 0. The material undergoes no physical polarization and directly enters the microchannel reactor tangentially in its normal, constant-phase state.
[0060] The difference between Comparative Example 4 and Example 1 is that the working reaction temperature inside the microchannel reactor was lowered to 100°C in the microchannel catalytic amination reaction.
[0061] The test results of the above examples and comparative examples are shown below. Example 2: Dichloroethane conversion rate 78.4%; polyamine selectivity 54.1%; cyclic byproducts 5.8 wt%; target distillate volume percentage 42.0%; metal loss rate 0.28 ppm. Example 3: Dichloroethane conversion rate 80.1%; polyamine selectivity 55.9%; cyclic byproducts 5.2 wt%; target distillate volume percentage 45.3%; metal loss rate 0.25 ppm. Example 4: Dichloroethane conversion rate 82.5%; polyamine selectivity 58.2%; cyclic byproducts 4.6 wt%; target distillate volume percentage 49.0%; metal loss rate 0.21 ppm. Example 5: Dichloroethane conversion rate 84.9%; polyamine selectivity 60.6%; cyclic byproducts 3.9 wt%; target distillate volume percentage 52.4%; metal loss rate 0.17 ppm. Example 6: Dichloroethane conversion 89.8%; polyamine selectivity 66.1%; cyclic byproducts 2.1 wt%; target distillate volume percentage 60.5%; metal loss 0.07 ppm. Example 7: Dichloroethane conversion 91.4%; polyamine selectivity 67.8%; cyclic byproducts 1.8 wt%; target distillate volume percentage 63.1%; metal loss 0.05 ppm. Example 8: Dichloroethane conversion 92.9%; polyamine selectivity 69.3%; cyclic byproducts 1.6 wt%; target distillate volume percentage 65.0%; metal loss 0.04 ppm. Example 9: Dichloroethane conversion 94.2%; polyamine selectivity 70.5%; cyclic byproducts 1.5 wt%; target distillate volume percentage 66.2%; metal loss 0.04 ppm. Example 10: Dichloroethane conversion rate 95.1%; polyamine selectivity 71.3%; cyclic byproducts 1.4 wt%; target distillate volume percentage 67.0%; metal loss rate 0.05 ppm.
[0062] Comparative Example 1: Dichloroethane conversion 62.3%; polyamine selectivity 31.4%; cyclic byproducts 16.7 wt%; target distillate volume percentage 23.5%; metal loss 0.85 ppm. Comparative Example 2: Dichloroethane conversion 85.0%; polyamine selectivity 57.3%; cyclic byproducts 4.2 wt%; target distillate volume percentage 50.1%; metal loss 3.42 ppm. Comparative Example 3: Dichloroethane conversion 51.6%; polyamine selectivity 45.0%; cyclic byproducts 8.9 wt%; target distillate volume percentage 31.2%; metal loss 0.12 ppm. Comparative Example 4: Dichloroethane conversion 40.2%; polyamine selectivity 41.7%; cyclic byproducts 9.5 wt%; target distillate volume percentage 20.8%; metal loss 0.10 ppm.
[0063] The results above show that, within the process limitations, Examples 1-10 maintained high conversion rates and linear selectivity when parameters were adjusted. A detailed comparative analysis of the test results, in conjunction with the accompanying figures, reveals the following specific patterns:
[0064] First, refer to Figure 2 The bar chart comparing reaction performance clearly demonstrates the kinetic contribution of reaction temperature in the pre-polarized cavity and microchannel reactor to the amination process. The stepwise increase in bombardment time, PVP dosage, polarization time, and temperature optimizes the catalyst surface defect density and spatial confinement effect, which is beneficial for promoting the amination reaction of the starting material molecules and inhibiting intramolecular deamination cyclization, thereby causing the product spatial distribution to shift towards the long-chain linear region. In Comparative Example 1, the elimination of plasma bombardment leads to a lack of oxygen vacancy defects in the support, weakening the selectivity for chemical bonds, causing the thermal condensation reaction trajectory to become uncontrolled, resulting in an increase in the formation of cyclic byproducts and a decrease in selectivity.
[0065] In comparison, such as Figure 2 As shown in the bar chart corresponding to Comparative Example 3, when the pre-linear dual external field fluid physical polarization cavity was removed, the total conversion rate of dichloroethane was only 51.6%, and the selectivity of high-boiling-point polyamines was only 45.0%, with the bar height significantly lower than that of Example 1. This confirms that pre-acoustic and microwave treatment improved the mixing, heat transfer, and temperature history of dichloroethane / ammonia water materials before entering the catalytic membrane, avoiding insufficient driving force for heterogeneous reactions at the interface. Figure 2 The results of Comparative Example 4 show that if the working reaction temperature of the microchannel catalytic amination reaction is excessively lowered to 100℃, the conversion rate of dichloroethane is reduced to the lowest level. This indicates that the temperature deviates from the activation energy range required for the heterogeneous catalytic amination reaction, which leads to a sharp decrease in the heterogeneous catalytic reaction rate in the microchannel, hinders the coupling thermodynamics of the target long chain segment, and reduces the conversion rate and the target distillate volume ratio to the lowest level.
[0066] Second, reference Figure 3The 50-hour long-term operational stability tracking line graph shown demonstrates the excellent anti-leakage performance of the catalytic membrane's internal space against polyamine chelation erosion. Figure 3 The comparison of the two time evolution curves shows that the solid line representing Example 1 remained in the low range of the parallel horizontal line throughout the entire evaluation period from 0 to 50 hours, with the cumulative total loss rate of active metals magnesium and titanium as low as 0.09 ppm at the 50-hour endpoint. However, the dashed line representing Comparative Example 2 showed an exponential increase in running time, with its metal loss increasing to 3.42 ppm at the 50-hour endpoint. These results indicate that Comparative Example 2, without the addition of exogenous polymer PVP, lacked the multidentate coordination locking of lactam groups and the barrier effect of the limited carbonized carbon network, leading to the loss of the heterogeneous catalyst's resistance to polyamine chelation erosion, resulting in a large loss of active metals magnesium and titanium and a deterioration in system operating stability. In contrast, Example 1 established a strong anti-chelation barrier, ensuring continuous and long-term operation.
[0067] Third, refer to Figure 4 The scatter plot of the evolution trend of the multivariate cascade reaction effect shows that as the process parameters from Example 2 to Example 10 are progressively increased, the conversion rate of dichloroethane increases stepwise, from 78.4% to a maximum of 95.1%; at the same time, the selectivity trend line of the high-boiling-point polyamine product also maintains an increasing trend from 54.1% to 71.3%; in stark contrast, the total mass fraction curve of cyclic amine byproducts shows a sharp and continuous decline. Figure 4 The results validated the multi-stage combination of the whole-process microchannel catalytic application system. By combining multiple temperature fields with strong physical polarization mass transfer, a continuous free thermal coupling growth path was opened up, which improved the yield of first-grade product while keeping cyclic amine byproducts such as piperazine at a low level.
[0068] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing a polyethylenepolyamine, characterized in that, The preparation method includes mixing dichloroethane with ammonia water and continuously injecting the mixture into a fluid physical polarization chamber for ultrasonic and microwave fluid physical polarization to obtain a polarized material fluid; continuously tangentially injecting the polarized material fluid into a microchannel reactor for catalytic amination reaction, wherein the inner wall of the microchannel of the microchannel reactor is coated with a Mg1Ti1 / v-Al2O3 heterogeneous catalytic membrane that has been pre-activated in situ in the liquid phase.
2. The method for preparing polyethylene polyamine according to claim 1, characterized in that, The preparation method further includes introducing the reaction fluid flowing out of the microchannel reactor into the subsequent catalyst-free thermal condensation section for continuous thermal coupling segment polymerization. The effluent is then diluted, desalted, solvent-removed, and subjected to vacuum distillation to obtain the polyethylene polyamine product.
3. The method for preparing polyethylene polyamine according to claim 1, characterized in that, The preparation method of the Mg1Ti1 / v-Al2O3 heterogeneous catalytic film is as follows: solid aluminum isopropoxide is heated and calcined in an argon atmosphere for 3-6 hours, cooled and ground to obtain alumina intermediate powder. The alumina intermediate powder was subjected to liquid-phase ultrasonic exfoliation in a mixed solvent of isopropanol and water for 4-10 hours to obtain two-dimensional Al2O3 nanosheets; the two-dimensional Al2O3 nanosheets were then sent into the cavity of an inductively coupled plasma device and subjected to argon gas for argon plasma directional bombardment and exfoliation for 5-25 minutes to obtain a modified alumina carrier. The modified alumina support was dispersed in anhydrous ethanol, and polyvinylpyrrolidone was added, with its mass controlled to be 4.0%-6.0% of the mass of the modified alumina support. The material temperature was controlled to be -5℃ to 5℃. A mixed metal salt aqueous solution with an atomic molar ratio of magnesium to titanium of 1:1 was added dropwise and a coordination reaction was carried out. After the coordination reaction was completed, the pH of the system was adjusted to 11.5, and hydrazine hydrate ethanol solution was added. Interfacial coordination and partial reduction induction were carried out at -5℃ to -5℃ for 2h to 4h. After the reaction was completed, the catalyst was washed by centrifugation, freeze-dried under vacuum, and finally subjected to solid-phase heat treatment at 300℃ to 600℃ under nitrogen protection for 4h to 6h to obtain the catalyst.
4. The method for preparing polyethylene polyamine according to claim 3, characterized in that, The conditions for the argon plasma directional bombardment and stripping treatment are: working pressure of the cavity 30Pa-50Pa, and working power set to 150W-350W.
5. The method for preparing polyethylene polyamine according to claim 1, characterized in that, The coating process involves mixing catalyst powder, binder, and rheology modifier in water to prepare a coating slurry, uniformly coating it onto the inner wall of the microchannel, and then drying and calcining it to form a catalytic film with a thickness of 50μm-100μm. Before introducing the main reactant, an ammonia solution containing potassium hydroxide is continuously pumped countercurrently into the microchannel for pre-activation, wherein the mass fraction of the ammonia solution is 25%-30% and the mass fraction of potassium hydroxide is 4%. The activation temperature of the control system is 85℃-95℃, and the activation treatment is continuously circulated and flushed for 2.0h-4.0h.
6. A polyethylene polyamine, characterized in that, The polyethylene polyamine is a mixed linear chain polyamine prepared using dichloroethane and ammonia as starting materials; the polyethylene polyamine is obtained by the preparation method described in any one of claims 1-5.